Uji Aktivitas Antibakteri Sediaan Hand Sanitizer Yang Di Produksi Secara Lokal Terhadap Bakteri Staphylococcus Aureus - asri wido mukti (Brawijaya University, 2021)
The increasing status of corona disease (Covid -19) to become a pandemic by WHO has caused people to panic buying for several medical equipment, which is Hand Sanitizer. Some individuals took the opportunity to benefit from making their own Hand Sanitizers whose formula was questionable because they did not have a distribution license and were traded freely in the marketplace so that their quality was questionable. Therefore, this study aims to determine the antibacterial activity of Hand Sanitizers which are produced without a distribution permit and are traded freely in the marketplace against S.aureus bacteria. The method used is by using the disc diffusion technique and the zone of inhibition is determined. This study uses a positive control in the form of a Hand Sanitizer which has a distribution license and an oil carrier as a negative control. Five samples of Hand Sanitizer was collected from marketplace based on their popularity and there are inhibition zones only in the sample code HS1 (70% alcohol and castor oil) and HS5 (70% alcohol) with an inhibition zone diameter of 1.8 mm and 4.3 mm which shows a growth inhibition response to bacteria S.aureus is very weak. It can be concluded that the antibacterial activity of this locally produced Hand Sanitizer is very weak in inhibiting S.aureus bacteria.